ECONOMIC ISSUES OF BROILER PRODUCTION LENGTH - Szőllősi, László; Szűcs, István; Nábrádi, András (Economics of Agriculture, 2014)
The length of broiler production cycle is also an important factor when proftability is measured. This paper is to determine the effects of different market ages and down-time period, overall broiler production cycle length on performance and economic parameters based on Hungarian production and fnancial circumstances. A deterministic model was constructed to manage the function-like correlations of age-related daily weight gain, daily feed intake and daily mortality data. The results show that broiler production cycle length has a signifcant effect on production and economic performance. Cycle length is determined by the length of down-time and grow-out periods. If down-time period is reduced by one day, an average net income of EUR 0.55 per m2 is realizable. However, the production period is not directly proportional either with emerging costs or obtainable revenues. Proft maximization is attainable if the production period is 41-42 days.